Citizen participation in the design of public policy through ICTs in Colombia - Bermeo Andrade, Helga Patricia; Calderon, Mónica; González-Bañales, Dora; Hernández, Iván (Cuadernos de Administración, 2018)
The growing development and social appropriation of ICTs nowadays represent a means that facilitates the participation of citizens in the design and management of public policies. The objective of this research was to assess the contribution generated by the use of a digital platform as a means to design and execute public policies aimed at strengthening the productive apparatus in the tourism and cultural industry of the Tolima region within the “Tolima Vive Digital”-TVD (Tolima Lives Digitally) project developed between 2013 and 2014 within the framework of the “Vive Digital” (Live Digitally) initiative by the National Government. Through an evaluative research model, structured surveys and in-depth interviews were applied to beneficiaries linked to the tourism and culture sector in the region, as well as to facilitators-experts in the operation of the platform. The results of the evaluation show the positive contribution of ICTs to the processes of citizen participation in the design of public policies by facilitating the participation and inclusion of citizens from remote regions, by enabling a more efficient systematization and integration of citizen demands and by generating a new communication channel between Government and citizens. In this way, the experience of the Tolima region represents a reference point for other government managers, and becomes a complementary contribution to the evaluation of the strategy for the digitalization of the public service in Colombia.